2017
DOI: 10.1155/2017/4587698
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Hsa_circ_00001649 in Gastric Cancer and Its Clinical Significance

Abstract: Background. It has been reported that circRNAs are differentially expressed in a wide range of cancers and could be used as a new biomarker for diagnosis. However, the correlation between circRNAs and gastric cancer (GC) it is still unclear. Materials and Methods. In this study, by using real-time quantitative reverse transcription-polymerase chain reactions (qRT-PCRs), we detected the expression level of hsa_circ_0001649 in tissue and serum samples from GC patients. Results. We found that hsa_circ_0001649 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…In GC, our group found that there were differences in the expression of hsa_circ_002059 between GC tissues and nontumor tissues and pairs of plasma samples before and after surgery . In another study, it was found that, compared with non‐tumor tissue, hsa_circ_0001649 was significantly downregulated in GC tissues, and its levels in serum samples of postoperative GC patients were significantly higher than those from preoperative patients . These results suggest that hsa_circ_002059 and hsa_circ_0001649 may be used as new biomarkers for GC.…”
Section: Tumor‐suppressive Circrnas May Be Used As Tumor Biomarkersmentioning
confidence: 94%
“…In GC, our group found that there were differences in the expression of hsa_circ_002059 between GC tissues and nontumor tissues and pairs of plasma samples before and after surgery . In another study, it was found that, compared with non‐tumor tissue, hsa_circ_0001649 was significantly downregulated in GC tissues, and its levels in serum samples of postoperative GC patients were significantly higher than those from preoperative patients . These results suggest that hsa_circ_002059 and hsa_circ_0001649 may be used as new biomarkers for GC.…”
Section: Tumor‐suppressive Circrnas May Be Used As Tumor Biomarkersmentioning
confidence: 94%
“…Among the included publications, a total of 43 articles on 64 studies were analyzed involving 10,123 subjects in Table . Of the 64 studies, five studies focused on colorectal cancer (Ji et al, ; Wang, Li, et al, ; Wang et al, ; Zhang, Yang, et al, ; Zhuo, Lin, Chen, Huang, & Hu, ), 10 on breast cancer (Lu et al, ; Yin et al, ), 22 on gastric cancer (Chen, Li, Zhao, Xiao, & Guo, ; Huang, He, Liang, Huang, & Zhu, ; Li, et al, , ; Li, Shao, et al, ; Li, Song, et al, ; Lu et al, ; Lu, Shao, Ye, Xiao, & Guo, ; Shao, Chen, et al, ; Shao, Li, et al, ; Shao, Yang, et al, ; Sun, Tang, et al, ; Tian, Chen, Li, & Xiao, ; Wei et al, ; Xie et al, ; Zhao, Chen, Li, Xiao, & Zhang, ), four on lung cancer (Li, Wang, Chen, Chen, & Jin, ; Zhu et al, ; Zong et al, ), 16 on hepatocellular carcinoma (Chen, Zhang, Lin, Song, & Wang, ; Fu et al, , ; Li et al, ; Qin et al, ; Shang et al, ; Yao et al, ; Yao et al, ; Zhang, Zhang, Lin, & Wang, ; Zhang, Zhou, et al, ; Zhang, Xu, et al, ) and seven on other cancers (Fan, Cao, Liu, Zhang, & Li, ; Lan et al, ; Li et al, ; Sun, Li, et al, ; Teng et al, ; Wang, Xue, et al, ; Yang et al, ). Moreover, three articles with 13 studies explored the diagnostic value of the combined circRNAs (Chen, Li, Zhao, et al, ; Fan et al, ; Li, Shao, et al, ) in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, because of their special advantages as biomarkers, circRNAs have attracted attention in the detection, diagnosis, and prognosis of cancers (Chen, Li, Zheng, et al, ; Jiang et al, ; Shang et al, ; Zhang et al, ; Zhu et al, ). First, dysregulation of circRNAs was identified in tissues, plasma, and even exosomes from patients with many types of cancer (Li, Song, et al, ; Lu et al, ; Shao, Chen, et al, ). Second, circRNAs possess conserved sequences and close stable loop structures (Jeck et al, ; Qu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, circ-CDC45 was identified enhanced in GM tissues than that in the normal tissues screened by circRNA microarray. *P < .05, **P < .01 and serum hsa_circ_0001649 in gastric cancer, 22 and so on. Nonetheless, other clinical characteristics were not related to the level of circ-CDC45.…”
Section: Discussionmentioning
confidence: 96%